Benzalkonium chloride disinfectant residues stimulate biofilm formation and increase survival of Vibrio bacterial pathogens - Mougin, Julia; Midelet, Graziella; Leterme, Sophie; Best, Giles; Ells, Timothy; Joyce, Alyssa; Whiley, Harriet; Brauge, Thomas (Frontiers in Microbiology, 2024)
Vibrio spp. are opportunistic human and animal pathogens found ubiquitously in marine environments. Globally, there is a predicted rise in the prevalence of Vibrio spp. due to increasing ocean temperatures, which carries significant implications for public health and the seafood industry. Consequently, there is an urgent need for enhanced strategies to control Vibrio spp. and prevent contamination, particularly in aquaculture and seafood processing facilities. Presently, these industries employ various disinfectants, including benzalkonium chloride (BAC), as part of their management strategies. While higher concentrations of BAC may be effective against these pathogens, inadequate rinsing post-disinfection could result in residual concentrations of BAC in the surrounding environment. This study aimed to investigate the adaptation and survival of Vibrio spp. exposed to varying concentrations of BAC residues. Results revealed that Vibrio bacteria, when exposed, exhibited a phenotypic adaptation characterized by an increase in biofilm biomass. Importantly, this effect was found to be strain-specific rather than species-specific. Exposure to BAC residues induced physiological changes in Vibrio biofilms, leading to an increase in the number of injured and alive cells within the biofilm. The exact nature of the “injured” bacteria remains unclear, but it is postulated that BAC might heighten the risk of viable but non-culturable (VBNC) bacteria development. These VBNC bacteria pose a significant threat, especially since they cannot be detected using the standard culture-based methods commonly employed for microbiological risk assessment in aquaculture and seafood industries. The undetected presence of VBNC bacteria could result in recurrent contamination events and subsequent disease outbreaks. This study provides evidence regarding the role of c-di-GMP signaling pathways in Vibrio adaptation mechanisms and suggests that c-di-GMP mediated repression is a potential avenue for further research. The findings underscore that the misuse and overuse of BAC may increase the risk of biofilm development and bacterial survival within the seafood processing chain.